2017
DOI: 10.5603/fm.a2017.0051
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the atrioventricular valves and related intraventricular structures in the wild pig (Sus scrofa)

Abstract: Morphology of the atrioventricular valves and the intraventricular related structures were observed and the findings were compared broadly to the literature, in the 7 hearts of the wild pigs (Sus scrofa) by applying macroscopic and microscopic techniques. In all hearts examinated, the tricuspid and mitral valves were precise, composing three and two cusps resepectively. The papillary muscles observed in mammalian heart in general were found in both the ventricles, additionaly there were small unnamed papillary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 35 publications
3
15
0
Order By: Relevance
“…In the present study, the septomarginal trabeculae of the bovine heart were a single muscular band that extends from the interventricular septum to the opposite right ventricular wall. It is in accordance with findings in studies using others species, such as pigs (Ateş et al, ; Gulyaeva & Roshchevskaya, ), dogs (Bombonato et al, ; Cope, ), camels (Ghonimi, Abuel‐Atta, Bareedy, & Balah, ), equines (Ghonimi et al, ; Halıgür & Dursun, ; Sathyamoorthy & Ramesh, ) and humans (Bandeira et al, ; Kosiński et al, ; Mamatha et al., ; Reig, Alberti, & Petit, ; Rocha et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In the present study, the septomarginal trabeculae of the bovine heart were a single muscular band that extends from the interventricular septum to the opposite right ventricular wall. It is in accordance with findings in studies using others species, such as pigs (Ateş et al, ; Gulyaeva & Roshchevskaya, ), dogs (Bombonato et al, ; Cope, ), camels (Ghonimi, Abuel‐Atta, Bareedy, & Balah, ), equines (Ghonimi et al, ; Halıgür & Dursun, ; Sathyamoorthy & Ramesh, ) and humans (Bandeira et al, ; Kosiński et al, ; Mamatha et al., ; Reig, Alberti, & Petit, ; Rocha et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…Histological studies have revealed more details regarding their functional correlations (Ravishankar, ). In this study, histological examination of the bovine septomarginal trabecula revealed the presence of the connective tissue, cardiac muscular fibres, blood vessels and Purkinje cells, in agreement with the histological aspect of trabecula in other animal species and in humans (Ateş et al, ; Bombonato et al, ; Ghonimi et al, ; Gulyaeva & Roshchevskaya, ; Sathyamoorthy & Ramesh, ).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations